β-Glucan-Producing Pediococcus parvulus 2.6: Test of Probiotic and Immunomodulatory Properties in Zebrafish Models - Pérez-Ramos, Adrián; Mohedano, Maria L.; Pardo, Miguel Á.; López, Paloma (Frontiers in Microbiology, 2018)
Lactic acid bacteria synthesize exopolysaccharides (EPS), which could benefit the host´s health as immunomodulators. Furthermore, EPS could protect bacteria against gastrointestinal stress, favouring gut colonization, thus protecting the host against pathogenic infections. Pediococcus parvulus 2.6, produces a 2-substituted (1,3)-β-D-glucan and, in this work, its probiotic properties as well as the immunomodulatory capability of its EPS have been investigated using Danio rerio (zebrafish). To this end and for a comparative analysis, P. parvulus 2.6 and its isogenic non-β-glucan-producing 2.6NR strain were fluorescently labelled by transfer of the pRCR12 plasmid, which encodes the mCherry protein. For the in vivo studies, there were used: (i) a gnotobiotic larvae zebrafish model for bacterial colonization, pathogen competition and evaluation of the β-glucan immunomodulation capability and (ii) a transgenic (mpx:GFP) zebrafish model to determine the EPS influence in the recruitment of neutrophils under an induced inflammation. The results revealed a positive effect of the β-glucan on colonization of the zebrafish gut by P. parvulus, as well as in competition of the bacterium with the pathogen Vibrio anguillarum in this environment. The larvae treatment with the purified β-glucan resulted in a decrease of expression of genes encoding pro-inflammatory cytokines. Moreover, the β-glucan had an anti-inflammatory effect, when it was evaluated in an induced inflammation model of Tg(mpx:GFP) zebrafish. Therefore, P. parvulus 2.6 and its EPS showed positive health properties in in vivo fish models, supporting their potential usage in aquaculture.